The TEL/ETV6 gene is required specifically for hematopoiesis in the bone marrow - Wang, Li Chun (Cold Spring Harbor Laboratory Press, 1998)
The TEL (translocation–Ets–leukemia or ETV6) locus, which encodes an Ets family transcription factor, is frequently rearranged in human leukemias of myeloid or lymphoid origins. By gene targeting in mice, we previously showed that TEL(−/−) mice are embryonic lethal because of a yolk sac angiogenic defect. TEL also appears essential for the survival of selected neural and mesenchymal populations within the embryo proper. Here, we have generated mouse chimeras with TEL(−/−) ES cells to examine a possible requirement in adult hematopoiesis. Although not required for the intrinsic proliferation and/or differentiation of adult-type hematopoietic lineages in the yolk sac and fetal liver, TEL function is essential for the establishment of hematopoiesis of all lineages in the bone marrow. This defect is manifest within the first week of postnatal life. Our data pinpoint a critical role for TEL in the normal transition of hematopoietic activity from fetal liver to bone marrow. This might reflect an inability of TEL(−/−) hematopoietic stem cells or progenitors to migrate or home to the bone marrow or, more likely, the failure of these cells to respond appropriately and/or survive within the bone marrow microenvironment. These data establish TEL as the first transcription factor required specifically for hematopoiesis within the bone marrow, as opposed to other sites of hematopoietic activity during development.